Chapter I «gomitoli del tempo». La poetica dello spazio nell'opera di Claudio Magris - MARFE', LUIGI (Biblioteca di Studi di Filologia Moderna, 2021)
Both in his novels, such as Illazioni su una sciabola (1984), Un altro mare (1991) and Alla cieca (2005), and in his travel writing, such as Danubio (1986), Microcosmi (1997) and L'infinito viaggiare (2005), Claudio Magris outlined a poetics of space that questions about the diachronic depth and the narrative meaning of places. The essay examines the topic of travel in Magris' work, as a means of metaliterary exploration, in order to reflect on the sense of history and on the identity of the writing subject.